Impact of Stunting on Development of Children between 1-3 Years of Age - Muhammad R. D. Mustakim, - (Research and publications office, Jimma University, 2022)
Abstract Background Stunting occurs due to chronic malnutrition and is a major problem for children in developing countries. It is important to evaluate the impact of stunting on the development of children. This study aimed to investigate the impact of stunting on the development of children between 1–3 years of age.